2017
DOI: 10.1155/2017/5913195
|View full text |Cite
|
Sign up to set email alerts
|

Biological Function of MicroRNA193a-3p in Health and Disease

Abstract: MicroRNAs (miRNAs) are a class of small noncoding RNAs that act mainly as negative regulators of gene expression. Several studies demonstrated that miRNAs take part in numerous biological processes, such as proliferation, apoptosis, and migration. The dysregulation of miRNAs has been frequently observed in different types of disease, including cancer. Here, we provide a comprehensive review on the human miR-193a-3p by considering its role in both physiological and pathological contexts. Different mechanisms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 61 publications
1
37
0
1
Order By: Relevance
“…Despite advances in the prevention, diagnosis and treatment of cSCC worldwide, the exact molecular basis of cSCC remains unclear ( 5 , 26 , 27 ). miRNAs are considered to be important genetic regulators of various biological processes, including cell proliferation, development, invasion and apoptosis ( 28 30 ). A number of previous studies have demonstrated that miRNAs are involved in the pathogenesis of a number of human diseases, particularly different types of cancer ( 12 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in the prevention, diagnosis and treatment of cSCC worldwide, the exact molecular basis of cSCC remains unclear ( 5 , 26 , 27 ). miRNAs are considered to be important genetic regulators of various biological processes, including cell proliferation, development, invasion and apoptosis ( 28 30 ). A number of previous studies have demonstrated that miRNAs are involved in the pathogenesis of a number of human diseases, particularly different types of cancer ( 12 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have recently become a focus of research. Their main function is post-transcriptional gene regulation in plants and animals (32)(33)(34), and studies have increasingly focused on their function in heart development (35)(36)(37). We identified previously that miR-29c-3p is upregulated in the serum of pregnant women carrying fetuses with CHD (9).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miRNAs have been used to target tumor-suppressor mRNAs or oncogene mRNAs [99]. The tumor-suppressor miRNA named miR-193a-3p has been demonstrated to affect proliferation, apoptosis, migration, invasion, and metastasis [100]. In another approach, it was demonstrated that HDAC inhibitors could modulate miR-200 expression, presenting a novel strategy having the potential for breast cancer treatment [101].…”
Section: Cancer and Epigeneticsmentioning
confidence: 99%